Analysis of salt accumulation in a forward osmosis system - Lay, Winson Chee Loong (2013)
An important issue concerning performance of forward osmosis (FO) systems is salt accumulation in the retentate. This occurs due to the highly retentive FO membrane and reverse diffusion of draw solutes. In this study, experimental data from an osmotic membrane bioreactor (OMBR), which epitomizes a challenging application for FO, was analyzed to investigate longer term effects of the above issue. It was found that salt accumulation is controlled by three factors: membrane, influent, and process. The role of the membrane is application-dependent and significant only when influent osmotic pressure is smaller or in the same order of magnitude as the salt to water permeability ratio (B/A). The study also shows that an experimental duration of 3 × solids retention time (SRT) is necessary for adequate study of salt accumulation in FO systems. Analysis of the B/A ratio provided fundamental information into system behavior. A reducing B/A could be associated with the formation of a mild secondary foulant layer, whereas an increasing B/A was observed for more severe fouling cases and indicated further flux reducing mechanisms. The study makes clear that knowledge of factors affecting salt accumulation is essential for optimization of FO systems.